Managerial Competence, Communication Skills, and Motivation: Impacts on Teacher Performance in Pidie Jaya Elementary Schools - Elida Fitri; Marwan Hamid; Saiful Bahri (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study investigates the impact of school management's administrative competence, interpersonal communication, and achievement motivation on teacher performance in public elementary schools within the Meurah Dua Subdistrict of Pidie Jaya Regency. Data were acquired from 128 teachers using a quantitative descriptive technique with a correlational survey design, employing total sampling. Questionnaires utilizing a Likert scale were administered, and the data were analyzed through Pearson correlation and multiple linear regression. The findings indicate that managerial competence significantly enhances teacher effectiveness, with the control function identified as the most prominent factor. Interpersonal communication exerts a beneficial yet rather modest impact on teacher effectiveness and achievement motivation. Achievement motivation substantially impacts teacher performance, with extrinsic motivation factors—especially income and incentives—exerting the greatest influence. Correlation study reveals moderate positive correlations between managerial competence and teacher performance (r = 0.482) and between achievement motivation and teacher performance (r = 0.391). Interpersonal communication exhibits a modest positive connection with teacher performance (r = 0.198). Managerial competence and achievement motivation strongly impact teacher effectiveness, although interpersonal communication exerts a relatively lesser influence. The study finds that augmenting management competency, fortifying effective communication, and cultivating intrinsic and extrinsic motivation are vital techniques for raising teacher effectiveness.